A Semantic Model to Assist Policy Refinement Mechanisms for NFV-MANO Systems - Bonfim, Michel; Freitas, Fred; Fernandes, Stenio (Anais do Workshop Pré-IETF (WPIETF); 2021: Anais do VIII Workshop Pré-IETF/IRTF, 2021)
Management in NFV scenarios is a complex task. In this scenario, automated policy refinement can be used to enforce NFV-MANO functions to deal with the increased complexity. However, existing solutions do not perform policy analysis. Therefore, in this work, we propose a semantic model in OWL 2, named Onto-Planner, to assist the policy refinement process for NFV-MANO systems. Preliminary results show that Onto-Planner provides policy analysis when a DL reasoner is applied.